Peran Kontribusi Sektor Kelautan dan Perikanan terhadap Produk Domestik Bruto (PDB) Indonesia - Gista Alfania Puri; Herlina Reva Carita; Haura Khalisa Hakim; Kayla Aryani Putri Nugroho; Khanaya Isyabrina Maryam; Ahmad Setiawan Nuraya (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The marine and fisheries sector plays a strategic role in Indonesia's national economy; however, its contribution to Gross Domestic Product (GDP) remains suboptimal due to challenges such as overfishing, illegal fishing, climate change, and low human resource quality. This study aims to analyze the contribution of the marine and fisheries sector to Indonesia's GDP and identify factors influencing its development. A qualitative descriptive approach was employed using documentation and literature review techniques based on secondary time series data for the 2020–2024 period sourced from BPS and KKP. The results indicate that the fisheries sector's GDP at constant prices increased steadily from IDR 254,112.3 billion in 2020 to IDR 292,559.1 billion in 2024, with the highest export volume reaching 1,425 thousand tons valued at USD 5.95 billion in 2024. Nevertheless, sector growth continues to face pressure from illegal fishing practices, ecosystem degradation, and limited human resource capacity. This study concludes that strengthening blue economy policies, enhancing international cooperation, and developing integrated human resources are strategic steps to optimize the marine and fisheries sector's contribution to sustainable national economic growth.